Predicting Cyberbullying–Cybervictimization Experience Based on Parent–Child Relationship, Psychological Well-Being, and Internet Addiction in Adolescents in Isfahan City - Gharagozloo, Zahra; Taheri Jebeli, Tayebeh; Dabiri, Solmaz; Ashrafifard, Somayeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to predict cyberbullying–cybervictimization experience based on parent–child relationship, psychological well-being, and internet addiction among adolescents in Isfahan City.Methods and Materials: The present study employed a descriptive-correlational design. The statistical population consisted of all male and female high school students enrolled during the 2024–2025 academic year in Isfahan City. Based on Morgan’s table, 382 students were selected using cluster random sampling. Data were collected using Young’s Internet Addiction Test (1998), the Cyber Bullying–Victimization Experience Questionnaire developed by Antoniadou et al. (2016), Ryff’s Short Form Psychological Well-Being Scale (1989), and Pianta’s Parent–Child Relationship Scale (2011). Data analysis was conducted using Pearson correlation coefficients and multiple linear regression analysis through SPSS version 27.Findings: The findings demonstrated that internet addiction had a significant positive relationship with cyberbullying–cybervictimization experience (β = 0.886, p < .001), whereas psychological well-being had a significant negative relationship with cyberbullying–cybervictimization experience (β = -0.154, p < .001). However, the overall parent–child relationship did not significantly predict cyberbullying–cybervictimization experience (β = -0.002, p = .959). The regression model was statistically significant (F = 208.95, p < .001) and explained 62.5% of the variance in cyberbullying–cybervictimization experience. In addition, the closeness component of the parent–child relationship showed a significant negative correlation with both cybervictimization and cyberbullying, whereas the conflict component demonstrated a significant positive correlation with these variables. No significant relationship was found between the dependency component and cyberbullying–cybervictimization.Conclusion: The findings indicate that internet addiction and psychological well-being are important predictors of cyberbullying–cybervictimization among adolescents. Excessive internet use may increase adolescents’ exposure to harmful online interactions, whereas higher psychological well-being may function as a protective factor against involvement in cyberbullying behaviors.